2013
DOI: 10.3389/fpls.2012.00310
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of proteomic studies towards understanding plant heavy metal stress response

Abstract: Modulation of plant proteome composition is an inevitable process to cope with the environmental challenges including heavy metal (HM) stress. Soil and water contaminated with hazardous metals not only cause permanent and irreversible health problems, but also result substantial reduction in crop yields. In course of time, plants have evolved complex mechanisms to regulate the uptake, mobilization, and intracellular concentration of metal ions to alleviate the stress damages. Since, the functional translated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(138 citation statements)
references
References 87 publications
6
126
0
1
Order By: Relevance
“…The mechanism of DNA alterations caused by metals in plants is unknown, but the lack of significant changes in DNA methylation in Acer rubrum plants exposed to nickel and copper contamination for over 30 years could be the result of a possible internal mechanism involved in metal ions processing in cells. In fact, plants can cope with metal through the sophisticated homeostatic cellular mechanisms that self‐regulate the content of metal ions in the cells to limit the negative impacts that result from exposure to nonessential metal ions (Hossain and Komatsu 2013). These mechanisms are used efficiently by some plant species to control metal uptake, mobilization, translocation, and detoxification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of DNA alterations caused by metals in plants is unknown, but the lack of significant changes in DNA methylation in Acer rubrum plants exposed to nickel and copper contamination for over 30 years could be the result of a possible internal mechanism involved in metal ions processing in cells. In fact, plants can cope with metal through the sophisticated homeostatic cellular mechanisms that self‐regulate the content of metal ions in the cells to limit the negative impacts that result from exposure to nonessential metal ions (Hossain and Komatsu 2013). These mechanisms are used efficiently by some plant species to control metal uptake, mobilization, translocation, and detoxification.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma membrane exclusion system and the synthesis of membrane transporters and thiol‐containing chelating compounds for vacuolar sequestration are the main methods used by plants to protect the cell from the adverse effects of metals. In addition, defense protein and molecular chaperones help plants growing in metal‐contaminated soil to maintain redox homeostasis (Hossain and Komatsu 2013). …”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown by several groups that protein levels do not always necessarily corresponds to mRNA levels. 36,37 Anderson et al, 38 reported that the correlation coefficient in quantity between mRNA and protein abundance is relatively low. Protein level can be modulated by changing either the rate of synthesis or the stability of the messenger RNA (mRNA or transcript), or the synthesis or stability of the protein itself.…”
Section: Proteomics: a Closer Look At Translatome Regulating Cellularmentioning
confidence: 99%
“…Yapılan bu proteomik analizler, ağır metal stresine cevap olarak bitki proteomunda meydana gelen değişimlerin anlaşılmasına katkıda bulunmuş olmasına rağmen, spesifik bir ağır metal için biyomarkörlerin teşhisini sağlayacak ileri çalışmalara gereksinim duyulmaktadır. Bu nedenle, ağır metallerin translokasyonu, transformasyonu, içsel alıkonulması ve hücre içerisinde bu metallerin detoksifikasyonunda muhtemel role sahip proteinlerin daha iyi tanımlanmasını sağlayacak proteomik üzerine yoğunlaşılması gerekmektedir Hossain and Komatsu 2013).…”
Section: Introductionunclassified